2016
DOI: 10.5194/isprsarchives-xli-b4-497-2016
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Calibration of the Clementine Uvvis Camera Using Images Acquired by the Lunar Reconnaissance Orbiter

Abstract: ABSTRACT:The Clementine UVVIS camera returned over half a million images while in orbit around the Moon in 1994. Since the Clementine mission, our knowledge of lunar topography, gravity, and the location of features on the surface has vastly improved with the success of the Gravity Recovery and Interior Laboratory (GRAIL) mission and ongoing Lunar Reconnaissance Orbiter (LRO) mission. In particular, the Lunar Reconnaissance Orbiter Camera (LROC) has returned over a million images of the Moon since entering orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Since the inclusion of feature matching into ISIS3, Becker and co-workers (2016) In addition, Speyerer et al (2016) used feature matching to calibrate the Clementine UVVIS camera system. In this study, they identified common features in UVVIS and LROC WAC observations acquired under similar lighting and viewing geometries.…”
Section: Objectivesmentioning
confidence: 99%
“…Since the inclusion of feature matching into ISIS3, Becker and co-workers (2016) In addition, Speyerer et al (2016) used feature matching to calibrate the Clementine UVVIS camera system. In this study, they identified common features in UVVIS and LROC WAC observations acquired under similar lighting and viewing geometries.…”
Section: Objectivesmentioning
confidence: 99%